Increasing trend in pediatric scrub typhus admissions in a tertiary care hospital, South India: Clinical profile and outcomes of cases over four years, 2011-2014. - K., Gandhimathi; Thekkur, Pruthu; Majella, Marie Gilbert; Selvaraj, Kalaiselvi; Chinnakali, Palanivel; Adhishivam, Bethou; Bhat, Vishnu B (International Journal of Contemporary Pediatrics, 2017)
Background: In developing countries, clinical profile based empirical treatment is practiced for treating pediatric scrub typhus cases. Knowledge on pattern of symptoms and signs will help in early initiation of specific treatment. This study was aimed to describe clinical profile and trends in admissions of pediatric scrub typhus cases in a tertiary teaching hospital. Methods: A record based cross sectional descriptive study was conducted among all clinically diagnosed scrub typhus pediatric (<13 years of age) cases admitted between 1st January 2011 and 31st December 2014 in a tertiary teaching hospital, South India. Data on symptoms, signs, laboratory findings, treatment and outcome were extracted from clinical case records. Data were entered and analyzed using Epi Data software. Results: Of the total 228 cases, 124 (54.4%) were males, 131 (57.4%) were less than five years of age and 88% were from rural areas. Fever (100%), vomiting (61.2%) and cough (54.8%) were the most common symptoms. Hepatomegaly (88.6%), splenomegaly (64.5%), lymphadenopathy (48.7%), edema (43.4%) and eschar (38.6%) were the common signs observed. Anemia was present in 122 (59.8%) and thrombocytopenia in 75 (33.3%) children. Only one child (0.4%) died. There was an increasing trend in proportion of scrub typhus cases to overall admissions from 1% to 2.2% over four-year period (2011-2014). More cases were admitted between the months of September and January. Conclusions:Scrub typhus contributed to significant pediatric admissions in the tertiary care centre with an increase in cases over years. Treatment with doxycycline or azithromycin showed good response and mortality was very low